2013
DOI: 10.1111/jpc.12392
|View full text |Cite
|
Sign up to set email alerts
|

Oral dextrose for analgesia in neonates during nasogastric tube insertion: A randomised controlled trial

Abstract: Oral D25 was effective in reducing the pain response during NGT insertion in neonates when compared with oral D10 and placebo. Oral D10 was not found to have a potent analgesic effect for the same.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 25 publications
5
11
0
1
Order By: Relevance
“…Mean gestational age in the present study was more when compared to study done by A Ravishankar et al, (36.4 weeks) and less when compared to study done by Chermont et al, (39 weeks). 21,22 Sex ratio among the cases in the present study was 1.27:1 and in controls was 1.08:1 which is comparable to studies done by Shreshta banga et al, (1.13:1) and A Ravishankar et al, (1:1). 21,23 Mean birth weight among cases in the present study was 2.96 kilograms(kgs) and in controls was 2.78 kgs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Mean gestational age in the present study was more when compared to study done by A Ravishankar et al, (36.4 weeks) and less when compared to study done by Chermont et al, (39 weeks). 21,22 Sex ratio among the cases in the present study was 1.27:1 and in controls was 1.08:1 which is comparable to studies done by Shreshta banga et al, (1.13:1) and A Ravishankar et al, (1:1). 21,23 Mean birth weight among cases in the present study was 2.96 kilograms(kgs) and in controls was 2.78 kgs.…”
Section: Discussionsupporting
confidence: 90%
“…21,22 Sex ratio among the cases in the present study was 1.27:1 and in controls was 1.08:1 which is comparable to studies done by Shreshta banga et al, (1.13:1) and A Ravishankar et al, (1:1). 21,23 Mean birth weight among cases in the present study was 2.96 kilograms(kgs) and in controls was 2.78 kgs. The mean birth weight was higher in cases than in controls which may be attributed to higher mean gestational age among cases.…”
Section: Discussionsupporting
confidence: 90%
“…However, there was no evidence of any benefit of the combination of glucose and non-nutritive sucking compared with glucose or non-nutritive sucking (Shah et al, 2015). Furthermore, Ravishankar et al (Ravishankar et al, 2014) also observed that infants receiving a glucose solution exhibited shorter crying times during nasogastric probe procedure. Studies have shown that patients who have used glucose solution exhibited lower crying intensity than did infants in the control group (Liu et al, 2010;Hall and Anand, 2014;Shah et al, 2015).…”
Section: Discussionmentioning
confidence: 92%
“…Studies have shown that patients who have used glucose solution exhibited lower crying intensity than did infants in the control group (Liu et al, 2010;Hall and Anand, 2014;Shah et al, 2015). Furthermore, Ravishankar et al (Ravishankar et al, 2014) also observed that infants receiving a glucose solution exhibited shorter crying times during nasogastric probe procedure. Similar analgesic effects were observed in studies using sweetened solutions (Liaw et al, 2011;Kassab et al, 2012;Sahoo et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Our search generated 45 studies and in 31 of these the source of pain was a routine heel prick or venepuncture. The other pain sources were two studies involving eye examinations; three involving endotracheal or nasal suctioning; three involving oro/nasogastric tube placement; and one each involving circumcision, intubation, transurethral catheterisation, hepatitis B vaccine injection, adhesive tape removal, arterial puncture and central vein catheterisation.…”
Section: Resultsmentioning
confidence: 99%